Vector Control of PMSM Take Over by Photovoltaic Source - T. Yuvaraja; K. Ramya, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This article established with the modeling and the field oriented control of permanent magnet synchronous machines, with a focus on their applications in variable speed domain in photovoltaic source.